Eu gosto de escutar música todo dia [...] Todo jovem gosta Escutar música já faz parte da minha vida: Jovens, escuta diária de música e aprendizagem musical - Popolin, Állisson (2012)
The purpose of this study was to identify what young students learn of music to experience it through the everyday experience of listening to music using digital technologies. It was developed in the field of music education in its social and cultural approach. Taking for granted that music is learned in daily activities, and that young people listen to music regularly, sometimes without intent to learn about music, the research question was: What young people learn about music in their daily musical experiences in listening mediated by technology today? The theoretical framework encompassed the theorization of Stockfelt (1997, 2004) in \"appropriate modes of listening highlighting how listening to music is an active experience, and stressing how complex is this musical practice. The methodological procedures were qualitative, but with some quantitative data. The techniques of data collection were a questionnaire, focus groups, semi structured focused interviews. The young people of the research were first year high school students at a public school in Araporã city, MG. All 51 young people from this school year of morning classes answered the questionnaire, 20 of them composed four focus groups and 16 were interviewed. The results indicated that young people who have played musical instruments expressed intention of learning more about music through their listening experiences. On the other hand the young people who have not played instruments, this intention was absent in much of the reporting. However, despite this non-intentionality, the young people demonstrated in their speech, gestures and attitudes have built knowledge of genres and musical styles (sounds, instrumentation, vocal timbre, rhythm, instrumental technique among others) as well as knowledge to use music in various situations of everyday life (regulation of mood, feelings, to do something to generate responses). Moreover, the practice of listening to music showed to be constituted of youth identity in aspects such as style, appearance, language, gestures and behaviors. This study contributed to understanding how the practice of listening to music mediated by technology happens among young people researched and what they learn from this experience. It was also visible among these young people that the experience of listening is active, broad and complex. The results of this investigation can help Music Education to broaden the conception of listening to music in the sense that it is not limited to a \"one right way, better or superior mode of listening\". They can also contribute to a broader music education that considers the dynamic modes of listening, their differences and characteristics, without a hierarchy among themselves.